Core–Shell Crystals of Porous Organic Cages. Issue 35 (10th June 2018) - Jiang, Shan; Du, Yi; Marcello, Marco; Corcoran, Edward W.; Calabro, David C.; Chong, Samantha Y.; Chen, Linjiang; Clowes, Rob; Hasell, Tom; Cooper, Andrew I.
Abstract: The first examples of core–shell porous molecular crystals are described. The physical properties of the core–shell crystals, such as surface hydrophobicity, CO2  /CH4 selectivity, are controlled by the chemical composition of the shell. This shows that porous core–shell molecular crystals can exhibit synergistic properties that out‐perform materials built from the individual, constituent molecules. Abstract : Synergistic properties : A defect‐free core–shell molecular cocrystal was constructed. It combines good CO2 adsorption capacity in the core with high CO2 /CH4 selectivity from the surrounding shell, and tunable surface hydrophobicity.